Neogeodynamics at northern prospect area of Petrikov potash deposit - Barbikov, Dzmitry V.; Kurlovich, Dzmitry M.; Kutyrlo, Vitali E. (Journal of the Belarusian State University. Geography and Geology, 2017)
The results of studies of neogeodynamics at northern prospect area of Petrikov potash deposit in Belarus are discussed. Endogenic and exogenic processes, active since the Late Oligocene have been studied with the complex of methods, including lineament and structural-geomorphological analysis. As a result of lineament analysis, it was determined that the most area of Northern prospect of Petrikov potash deposit is stable in terms of geodynamics. The zones of potential development of neogeodynamic processes occupy only 20 % of the area of prospect. These zones are referred to areas of weakened earth crust, within which higher fracturing of rocks may occur. Based on the results of structural-geomorphological analysis, geodynamic active structures and lineament are revealed. Geodynamic activity of the territory since the end of Middle Pleistocene is defined. During the period from the end of Middle Pleistocene to Holocene, a weak intensity of geodynamic processes occurred for 54 % of total area of Northern prospect, a moderate intensity was registered for 33 %, and higher than moderate and high intensity was characteristic for 13 % of total area. In Holocene a weak intensity of recent geodynamic processes is registered for 78 % of the research area, moderate intensity is relevant to 9 %, and higher than moderate intensity is recorded for 3 % of study area. The received results are considered at design and construction of especially important engineering constructions of Petrikovsky ore-dressing and processing enterprise.
Keywords: geodynamics; lineament; lineaments density; morphostructures; neogeodynamic active structures; zones of neogeodynamic activity; geographic information systems